PHILOSOPHICAL ANALYSIS AS A WAY OF RESEARCHING OF PROFESSIONAL EDUCATION PROBLEMS - Бех, В. П.; Бех, Ю. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article deals with the content of the philosophical analysis of the problems of professional education, comprising the identification of the nature of the phenomenon, its essence, content, forms, worldview and cognitive ideology, person’s place in it and modeling the selfreproduction mechanism.